Compact RF/ Laser Dielectric Linacs for Internal and External Cancer Therapy and Dynamic DNA Damage/Repair Analysis - Uesaka, M.; Pohl, M.; Miyoshi, K.; Inoue, Y.; Takahashi, T.; Ozeki, M.; Kamei, S.; Jang, J.; Yoshida, M.; Koyama, K.; Ikeda, T. (Recent Developments in Engineering Research Vol. 12, 2021)
We are performing three-staged development of compact linear accelerators (hereafter linac) with S-band (2.856 GHz, wavelength 105 mm), X-band (9.3 GHz, 32.3 mm) RF (Radio frequency) and Yb fiber laser (283 THz, wavelength 1.06 mm). Recently, we have proposed S-band 40 MeV 40 kW linac for Medical RI (Radioisotope) production of 99Mo/99mTc (g-emitter), 67Cu (b+) and 225Ac (a). X-band 6 MeV linac have been made for pinpoint X-ray dynamic tracking cancer therapy. The electron beam size at the X-ray target is less than 1 mm and X-ray spot size at the cancer is less than 3 mm. Several hardware and software are under construction for dynamic tracking Radiation Therapy (RT) for moving lung cancer. Moreover, as an ultimate compact linac, we are designing and manufacturing a laser dielectric linac of ~1 MeV with Yb fiber laser. Since the wavelength is 1.06 mm, the length of one accelerating structure is tens mm and the electron beam size is ~ 1mm. We plan to use this “On-chip” linac for radiation-induced DNA damage/repair analysis since the sizes of cell and nucleus are about 10 and 1 mm, respectively. We are thinking a system where DNA in a cell nucleus is hit by ~1 mm electron- and ion-beams and observe its repair by proteins and enzymes in live cells in-situ. Finally, we try to contribute to advanced radiation biological research for theranostics (= therapeutics and diagnostics).